Communication strategy in licensing services through the Jakarta evolution application (Jak Evo) - Fina Yunita Sari; Nurliah Nurdin; Petrus Polyando (Sean Institute, 2024)
This research was motivated by the ineffective internal communication of the Investment Management Unit and One Stop Integrated Services (UPPMPTSP) Pasar Minggu District, in licensing services via the Jakarta Evolution Application (Jak Evo) to the Applicant. This research aims to analyze and find out what the Communication Strategy is in licensing services through the Jakarta Evolution (Jak Evo) Application in the Investment Management Unit and One Stop Integrated Services (UP PMPTSP) Pasar Minggu District. This research uses descriptive qualitative methods. The data sources used are primary data and secondary data. Data collection techniques through observation, interviews and documentation. Data analysis method using data reduction, data presentation and drawing conclusions. The results of this research show that there are several factors that influence communication in licensing services via the Jakarta Evolution (Jak Evo) Application in UP PMPTSP, Pasar Minggu District, which is not yet effective. One of them is a problem in setting up the notification system which affects the efficiency and responsiveness of the service. Technical and managerial improvements are needed to ensure timely and accurate notifications. In addition, there is a need to expand communication channels to cover less reached groups through social media as well as pay attention to various media formats to ensure accessibility of information to all groups of society. Based on research findings, the right strategy is improving the notification system, managing human resources (HR), expanding the reach of socialization, strengthening socialization through social media, as well as continuous evaluation and improvement. This strategy aims to increase public understanding and adoption of the Jak Evo application with a more targeted, comprehensive and inclusive approach.